EVALUATION OF BIOGAS POWER POTENTIAL FROM CO-DIGESTION OF FOOD WASTE AND PALM OIL MILL EFFLUENT - Samuel Batet and Efe Justic Igbagbon (International Research Journal of Modernization in Engineering Technology and Science, 2025)
Nigeria's growing population has significantly increased the country's ongoing need for a conveniently available, renewable energy source. In order to produce biogas and produce electricity, food waste and palm oil mill effluent were co-digested in this study. The materials used in this study include food waste, palm oil mill effluent, plastic bottle bio-digester, and mercury-in-glass thermometer. Using a 25-liter plastic container as the batch reactor, the fresh ground POME and food waste were co-digested and digested at a mesophilic temperature range of 29 to 37°C. The hydraulic retention time was 25 days, according to the results. In other words, the first seven days of anaerobic digestion without biogas yields and 25 days of continuous biogas yields spaced two days apart. On the 25th day, minimum biogas yields were attained. On the 21st day, however, the highest biogas yield was achieved. The completion of digestion was the cause of the decrease in biogas production on the 25th day. According to the examination of biogas yields, food waste, POME, and co-digested POME and food waste produced an average of 0.00707 m³, 0.00724 m³, and 0.00965 m³ of biogas. Therefore, the maximum increased biogas yield is provided by the co-digested feedstock. Likewise, the average amount of electricity produced by the co-digested feedstock is 0.01516 kWh. Therefore, a portion of Nigeria's energy and waste issues can be resolved with the appropriate use of biogas technology. Keywords: Biogas, Food Waste, Effluent, Co-digestion, Electricity, Mesophilic Temperature.
The demand for energy consumption and waste generation in Nigeria necessitates the adoption of technologies that promote renewable energy and the conversion of wastes into viable commodity.
Keywords: Biogas; Food Waste; Effluent; Co-digestion; Electricity; Mesophilic Temperature